DEVELOPMENT OF DIGITAL COMPETENCE OF TEACHERS OF GENERAL EDUCATION DISCIPLINES (Innovative professional education, 2024)
The author highlights the experience of the Educational and Methodological Center of Vocational and Technical Education in Luhansk Oblast during the war, aimed at supporting displaced institutions of vocational (vocational and technical) education, developing the digital competence of teachers of general education disciplines.
Keywords: digital competence, displaced institutions of vocational (vocational and technical) education, teachers of general education disciplines, educational and methodological center of vocational and technical education, distance learning